Electrical and photoelectronic properties of hexagonal GaN - Seitz, R.
Photoconductivity of a non-intentionally doped GaN layer is observed for above band gap excitation. No below band gap excitation causes photoconductivity, but photoconductivity is optical quenched at energies of 1.28, 1.41, 1.53 and ≈2eV. The dark current and the yellow photoluminescence band show the same activation energy (42 meV) supporting therefore the model that relates the yellow band to a shallow donor to a deep acceptor transition. The photocurrent is thermally quenched with an activation energy of 77 meV.